The IVP Bible background commentary : New Testament - Keener, Craig S., 1960- (InterVarsity Press, 1993)
Why was labeling the Pharisees "white-washed tombs" one of the strongest criticisms Jesus could have made? Why were the disciples, after Jesus' death and resurrection, determined to replace Judas and keep their number exactly at twelve? What is the background to Paul's denunciation of homosexual behavior? Why did Paul expect Corinthian women to cover their heads? These and hundreds of other similar questions arise for anyone who reads and tries to live by the Bible. Today's world is very different from the Greek, Roman and Jewish world of Jesus and the New Testament writers. Scholars devote their lives to the study of languages, archaeology and history in order to better understand the Bible and its cultures. But often the results of their studies are found only in academic libraries. For the first time, Craig Keener's Bible Background Commentary: New Testament provides the fruit of scholarly labors in a single volume arranged in convenient verse-by-verse format, covering the entire New Testament. Based on ten years of in-depth study, the Bible Background Commentary will be valuable for pastors in sermon preparation, for Sunday-school and other church teachers as they build lessons, for missionaries concerned not to import their own cultural biases into the Bible, for college and seminary students in classroom assignments, and for everyday Bible readers seeking to deepen and enhance their study of Scripture.